Analisis Wacana Kritis terhadap Tagline “Indonesia Gelap” dalam Pemberitaan Kompas.com - Reza Mehdi Fauzi (Journal of Innovative and Creativity, 2025)
This research analyzes the critical discourse construction of the tagline "Dark Indonesia" in Kompas.com news reporting using Norman Fairclough's three-dimensional model. Through a qualitative approach with critical paradigm, this study reveals that the tagline "Dark Indonesia" constitutes a complex discursive construction with strong ideological content. At the textual dimension, the use of conceptual metaphor "dark" versus "light" creates evaluative binarism that simplifies the complexity of Indonesian history into moral dichotomy. Discourse practice analysis shows that the use of this tagline reflects systematic and targeted editorial positioning, utilizing digital media characteristics for optimal distribution and engagement. At the social practice dimension, this tagline operates within the context of post-Reform political transformation and functions as an instrument for collective memory formation supporting democratic values. Findings indicate that this discourse construction has ambivalent implications: positively contributing to democratic consolidation on one hand, while potentially hindering critical thinking and creating political polarization on the other. This research emphasizes the importance of critical media literacy in the digital era to help society become more reflective media consumers who are not easily manipulated by mass media ideological bias.